Efficient robot navigation inspired by honeybee learning flights - Dequan Ou; Jesse J. Hagenaars; Maciej R. Jankowski; Michiel V. M. Firlefyn; Christophe De Wagter; Florian T. Muijres; Jacqueline Degen; Guido C. H. E. de Croon (Nature, 2026)
Abstract Navigation is a crucial capability for both animals and robots. Although tiny flying insects can robustly navigate over long distances 1 , state-of-the-art robot navigation methods are computationally expensive and therefore restricted to large robots 2,3 . Here we propose ‘Bee-Nav’, a highly efficient navigation strategy inspired by the visual learning flights of honeybees 4–6 . In equivalent robotic learning flights, a tiny neural network is trained to map omnidirectional images to a home vector based on path integration. After learning, the robot can fly far away from home, come straight back using path integration and cancel integration drift using the visual homing network. Simulations showed that, for realistic path integration accuracies, the neural network requires training on only approximately 0.25–10.00% of the total flight area. In real-world indoor and outdoor experiments, a small drone successfully returned to within 0.5 m of home for 100% of 30–110-m flights and 70% of 200–600-m flights in windy conditions, using 3.4-kB and 42-kB neural networks, respectively. The proposed navigation strategy will be vital for resource-constrained robots that perform tasks while travelling from and to a home location. Furthermore, it provides new perspectives on the neuroethology of insect navigation, from how visual learning shapes homing trajectories to the nature of cognitive maps.